Effect of Blended NPSB and Nitrogen Application rates on Growth, Yield, and Yield Components of Bread Wheat (Triticum aestivum L.) at Gitilo Dale Research Site of Wallaga University, Western Ethiopia - Delesa Abdisa Jalata; Amsalu Gobena Roro; Adugna Hunduma Dabalo; Fayera Asefa Bebayehu; Abdela Tufa Woticha (Advances in Agriculture)
Wheat (Triticum aestivum L.) is a very important cereal crop widely produced and consumed in almost all parts of Ethiopia. However, due to abiotic and biotic stresses, its productivity is low as compared to the world average. Among these, soil fertility and unbalanced application of plant nutrients are the major constraints that limit the productivity of the crop in sub-Saharan African countries especially Ethiopia. As a result, an experiment was carried out at the Gitilo Dale Research Site of Wallaga University to determine the combined impact of blended NPSB and urea fertilizers on the growth, yield, and yield-related variables of bread wheat. The experiment used a factorial-arranged in randomized full block design with two factors with four levels each: NPSB (0, 100, 150, and 200 kg·ha−1) and nitrogen (urea) (0, 31.1, 71.65, and 112.2 kg·ha−1) (RCBD). With three replications, there were sixteen treatments. A test crop of the bread wheat variety liben (ETBW 5653) was grown. The phonological and growth parameters of bread wheat were significantly affected by NPSB and nitrogen applications as well as their interactions except for days to 50% emergence. The primary and interaction impacts of NPSB and nitrogen rates affected the yield and all of its constituents, except the number of kernels per spike. The application of 200 kg·ha−1 NPSB plus 112.2 kg·ha−1 nitrogen treatment resulted in the highest above-ground biomass production of bread wheat (12481.00 kg·ha−1), grain yield of 5182.51 kg·ha−1, and a straw yield of 7298.40 kg·ha−1. Hence, to maximize the yield of bread wheat, applying 200 kg·ha−1 of chemically blended NPSB with 112.2 kg·ha−1 nitrogen is recommended rather than applying any straight and complex fertilizers having only macronutrients.